Pengaruh Model Project Based Learning Terhadap Kemampuan Penalaran Matematis Penyajian Data Kelas V Sekolah Dasar - Melsi Libra Sari; Melva Zainil (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
This research aims to determine the effect of the Project Based Learning model on themathematical reasoning ability of data presentation in 5th grade class of Elementary School. This type of research used quasi experiments (quasi experimental design). The design used was Nonequivalent Control Group Design. The sampling technique used cluster random sampling, which targeted population consisted of several elementary schools in Gugus 1 of Lubuk Begalung sub-district Padang City. The amount samples of this study are 56 students in 5th grade class of 36 Cengkeh  and 33 Tanjung Sabar Public Elementary Schools in Padang City. The instruments used in this research were tests based. According on the data analysis that has been done, the results of the study show that there is an effect of mathematical reasoning ability in the presentation of data at 5th grade class of 36th State Primary Schools Cengkeh. This is proven from the acquisition of thitung = 3,1> ttabel= 2,0063 with a real level of 0.05 and dk = 54,  which means Ha is accepted and Ho is rejected, it can be concluded that the Project Based Learning model has a significant effect on mathematical reasoning ability in the data presentation of students 5th grade elementary school.